APLIKASI REPORTING IMAGE DENGAN METODE LOCATION BASED SERVICES BERBASIS ANDROID - Herman Kuswanto; Muhamad Ryansyah; Muhamad Arba (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Android is a software platform for mobile devices supported by Google OS. Android uses a modified version of the Linux kernel that is able to be distributed openly (open source). This makes it possible for developers to manage, modify and create their own applications. Mapping application is an application regarding geography that has been developed. This report system application is used to provide reports or information in the form of an image along with the location of the selected object. This encourages the writer to make an Android-based imagereporting application. This ireporting application is made using Android Studio tools that have SDK and JDK installed and then uses a system from Google Cloud to correlate the database to the platform. While the programming languages used are Java, XML, and SQL Lite. The research method used is the SDLC (Software Development Life Cycle) which consists of an identification phase, an analysis phase, a design phase, a trial phase. This application will get information and visualization of objects in the form of maps that can be used as a reference for Android mobile device users in making decisions, especially in giving reports or information objectively and efficiently. In addition, it can find the direction radius at the initial location to the final location, and there is also a favorite menu for storing complex and correct reports, other supporting menus.